Perspektif Fikih Islam Terkait Ṣulḥ Fuḍūlī dalam Proses Perdamaian Pihak Bersengketa - Nico Akbar; Rapung Rapung; Awal Rifai (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2024)
Sulh fuduli is a peace-making effort conducted by a third party without formal authority. In Islamic jurisprudence, the legitimacy of sulh fudhuli is recognized, though there are differences among jurists across various schools of thought regarding its specifics, procedures, and conditions. This study aims to understand the perspectives of Islamic jurists on Sulh Fuduli in the peace process between disputing parties, using a qualitative research approach and literature review method. The results of this research indicate that Islamic jurists have significant views on the role of third parties in the peace process to resolve disputes, analyzing arbitration and conciliation sulh. In this context, it is important to understand the concepts of peace, dispute, and mediation in Islam, and to maintain legitimate peace objectives in accordance with religious principles. Consequently, this study contributes to the understanding of the role of third parties in creating harmonious peace within society. The application of this concept is also discussed in the contexts of trade and marriage, showing analogies between unauthorized transactions in various types of contracts. Classical literature emphasizes that peace made by a third party can be considered legitimate in certain situations where such peace provides benefits to the defendant and does not harm the involved parties.